Arithmetic
Arithmetic Progression
Associative Property
Averages
Brackets
Closure Property
Commutative Property
Conversion of Measurement Units
Cube Root
Decimal
Distributivity of Multiplication over Addition
Divisibility Principles
Equality
Exponents
Factors
Fractions
Fundamental Operations
H.C.F / G.C.D
Integers
L.C.M
Multiples
Multiplicative Identity
Multiplicative Inverse
Numbers
Percentages
Profit and Loss
Ratio and Proportion
Simple Interest
Square Root
Unitary Method
Algebra
Cartesian System
Order Relation
Polynomials
Probability
Standard Identities & their applications
Transpose
Geometry
Basic Geometrical Terms
Circle
Curves
Angles
Define Line, Line Segment and Rays
Non-Collinear Points
Parallelogram
Rectangle
Rhombus
Square
Three dimensional object
Trapezium
Triangle
Trigonometry
Trigonometry Ratios
Data-Handling
Arithmetic Mean
Frequency Distribution Table
Graphs
Median
Mode
Range

Videos
Solved Problems
Home >> Polynomials >> Find Value of Polynomial >>

## Find Value of Polynomial

 Algebraic Expression Algebraic Equation Ordering of Polynomials Types of Polynomials Addition of Polynomials Subtraction of Polynomials Multiplication of Polynomials Division of Polynomials Types of Degree / Powers in Polynomials Difference between Polynomials of Integers & Rationals Find Value of Polynomial Find Zero of Polynomial Remainder Theorem in Polynomial Linear Equations Quadratic Equation Factoring of Quadratic Polynomials

 Value of a polynomial is obtained when variables of given polynomial are interchanged or replaced by the value of variable. Let's study the following examples to understand with the help of below examples: Example 1: Find the value of following polynomial where x = 2 p(x) = x2 + 4x + 4 Solution: Given polynomial: p(x) = x2 + 4x + 4 Value of given polynomial when x = 2 and we get: p(2) = (2)2 + 4 (2) + 4 Solve exponential forms and we get: = 4 + 8 + 4 Solve the addition expression and we get: = 16 Hence the value of p(x) = x2 + 4x + 4, where x = 2, is 16 Example 2: Find the value of following polynomial where y = 1 p(y) = 2y3 + y2 + 3 Solution: Given polynomial: p(y) = 2y3 + y2 + 3 Value of given polynomial when y = 1 and we get: p(1) = 2 (1)2 + (1)2 + 3 Solve exponential forms and we get: = 2 + 1 + 3 Solve the addition expression and we get: = 6 Hence the value of p(y) = 2y3 + y2 + 3, where y = 1, is 16 Example 3: Find the value of following polynomial where a = -2 p(a) = a3 + a2 - 10 Solution: Given polynomial: p(a) = a3 + a2 - 10 Value of given polynomial when a = -2 and we get: p(-2) = (-2)3 + (-2)2 - 10 Solve exponential forms and we get: = (-8) + 4 - 10 Solve the above expression and we get: = (-18) + 4 = (-14) Hence the value of p(a) = a3 + a2 - 10, where a = -2, is (-14)

Copyright@2022 Algebraden.com (Math, Algebra & Geometry tutorials for school and home education)